DARI DESA MENJADI OBJEK WISATA UTAMA: PERAN OBJEK WISATA DAN PAKET WISATA BUDAYA SEBAGAI KATALIS EKONOMI DI DESA BATUAN - Wijayanti, Ni Putu Evi; Komang Kesava Mahardika Putra; Veronica (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
This study analyzes the role of culture-based tour packages in community economic growth at Batuan Village, Bali. Batuan Village has a big potential as a tourist attraction, however it is not optimally used. The sculpture art, batuan style painting, and our traditional dance believed to be capable of attracting tourists, especially to tourists that love the authentic experience. This study used a combination of two methods (Mix-method). Between qualitative by interview, and quantitative by data. The result of this study is community empowerment and local artists as a tour guide is an effective strategy. Art activist utilization gave an opportunity for community economic growth and cultural sustainability of Batuan Village. Thus, culture-based has a potential to become a great strategy for Batuan Village as a leading tourist attraction.